Determinant of Dividend Payout Ratiosin Consumer Goods Company - Yeko Fongky Chaniago; Agustin Ekadjaja (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this study was conducted to determine the effect of return on equity,cash ratios and managerial ownership on dividend payout ratios in consumer goods company listed on the Indonesian stock exchange (IDX) in the period 2017-2020. This study uses 15 companies sample from 53 company data were selected using purposive sampling method. The results of the study partially show that return on equity and managerial ownership have a significant and positive effect on the dividend payout ratio, while the cash ratio show positive but not significant results on dividend payout ratio in consumer goods company listed on the Indonesian stock exchange (IDX) in the period 2017 -2020 . Simultaneously, return on equity, cash ratio and manajerial ownership have a significant effect on dividend payout ratio in consumer goods company listed on the Indonesian stock exchange (IDX) in the period 2017-2020 .